2022
DOI: 10.3389/fmed.2022.720551
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Atraumatic Shoulder Conditions: Protocol for a Systematic Review and Meta-Analysis

Abstract: IntroductionShoulder pain is one of the most common musculoskeletal disorders among adults and is caused by a variety of shoulder conditions. The popularity of different acupuncture methods in the nonsurgical treatment of shoulder pain has recently increased. However, evidence regarding the efficacy of acupuncture for shoulder pain is inconsistent, and there is a lack of supporting evidence regarding the overall efficacy of different acupuncture methods for shoulder pain.Methods and AnalysisA systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain. Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain. Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“… 13 In addition, no clear conclusion has yet been reached on whether acupuncture treatment provides additional benefit to exercise in SIS. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%